Karl Marx's theory of ideas - Torrance, John. (Cambridge ; New York : Cambridge University Press, 1995)
Marx's ideas about how society presents a misleading appearance to its members have been the subject of many conflicting interpretations. In this book John Torrance takes a fresh, un-Marxist approach to Marx's texts and shows that a more precise, coherent and cogent sociology of ideas can be extracted from them than is generally allowed.
The implications of this for twentieth-century capitalism and for recent debates about Marx's conceptions of justice, morality and the history of social science are explored. The author argues that Marx's theory of ideas is sufficiently independent of other parts of his thought to provide a critique and explanation of those defects in his own understanding of capitalism which allowed Marxism itself to become, by his own definition, an ideology.
Bibliography of works by Marx and Engels -- 1. Marxism versus Marx: what Marx's theory of ideology was not -- 2. Marx's theory of knowledge -- 3. The basis of false consciousness: theory -- 4. The basis of false consciousness: social being -- 5. Social consciousness -- 6. Ideology -- 7. Class struggle, consciousness and ideology -- 8. Justice -- 9. Morality -- 10. The sociology of political economy -- 11. Marx's science and Marxist ideology.
Includes bibliographical references (p. 428-430) and index.
Keywords: Marx, Karl, -- 1818-1883.; Idea (Philosophy); Ideology